DESIGN OF FREQUENCY SELECTIVE LIMITING CIRCUIT - Zahriladha, Zakaria (2012)
This paper explains the design of frequencyselective limiting circuit. The circuit is typically based on nonlinear matched reflection-mode bandstop resonator. This type of Frequency Selective Limiters achieves fast switching, high-level of power limiting, and flexible channel bandwidth. For single channel limiting, a device with one resonator (first order) produced a band-stop response centred at 2 GHz with 250 MHz of limiting bandwidth, 0 dBm limiting threshold, and 32 dB limiting level and it gave an all-pass response with less than 2.5 dB insertion loss at low RF powers. Multi-resonator filter has been used inorder to improve the performance of the device. The prototype will produce intermodulation distortions and response time. Simulated results show an excellent highly selective bandstop performance at high powers with a near all-pass response at low signal powers.